Augmented Reality’s Role in Highlighting Historical Heritage / Kirkuk Citadel (Journal of Engineering, 2023)
Augmented Reality (AR) is one of the technological developments in recent years that uses the real world as a basic pillar and enhances it by overlaying virtual objects created by computers. The study provides an overview of the use of augmented reality technology in meeting one of the most important requirements of cultural tourism: highlighting cultural and historical heritage. Accordingly, the research problem concentrated on the lack of local literature associated with the use of augmented reality in cultural tourism. It aimed to fill this gap by building a knowledge base and demonstrating the potential of augmented reality in this field. Hence, the importance of research in drawing the attention of tourism practitioners to the importance of augmented reality and discovering its potential. The research discusses the topics of cultural heritage, cultural tourism, augmented reality, and the study of its potential and applications in tourism. Augmented reality capabilities from the theoretical framework have been applied to Kirkuk Citadel -as a case of study- through the application of a proposal by the researcher for Kirkuk Citadel. The research concludes that augmented reality is an interactive scientific guide that supports the tourist, meets his cultural needs, and positively impacts the quality of tourism and tourist attractions.The study is part of an ongoing research project aimed at developing the tourism of historic city centers through augmented reality technology.